Problems of Integration of North and South Yemen in the Context of Regional Political Processes - Annikova, V A; Hussein, M K (Vestnik Rossijskogo universiteta družby narodov. Seriâ Politologiâ (Online), 2016)
The authors of the article attempt the analysis of multilateral political and historical reasons for the opposition of North and South Yemen and the complete as well as the probable consequences of further escalation of the conflict on the Arabian Peninsula and the entire Middle East region.